Searching for a "Golden Rule" of Economic Regulation of an Infectious Disease - Eirik S. Amundsen (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates whether a "Golden Rule" of regulation of an infectious disease may be elicited that balances the economic control and disease costs when the arrival of a future vaccine or a cure is uncertain. Formulating an optimal control problem applied to standard compartment models of infection, an optimality rule is derived. This rule is more complex than other similar Golden Rules related to optimal economic growth or extraction of natural resources. The paper contains interpretation of the derived rule and numeric examples of how the rule functions under the compartment models (i.e., the SI, the SIS, and the SIR models).
Keywords: H51; I18; 330; infectious disease; economic regulation; Golden Rule; compartment models